2021
DOI: 10.1111/jtxs.12584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fat content on the textural and in vivo buccal breakdown properties of soy yogurt

Abstract: This study aimed to evaluate the effects of fat content on the textural and in vivo buccal breakdown properties of soy yogurt (SY) at different pH (5.4, 5.0, and 4.6). The microbial analysis, textural and rheological properties, and interfacial protein composition of all the samples were monitored. Microbial results suggested that the increased fat content in SY‐5.0 and SY‐4.6 resulted in significantly high viable cell counts of lactic acid bacteria (LAB). Textural studies demonstrated that the presence of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This finding confirms the dependence of LAB activity on microbial density and fermentation medium. pH is a crucial element in the fermentation process that defines the textural characteristics of soy yoghurt and serves as a crucial signal for the growth of LAB (Shen et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This finding confirms the dependence of LAB activity on microbial density and fermentation medium. pH is a crucial element in the fermentation process that defines the textural characteristics of soy yoghurt and serves as a crucial signal for the growth of LAB (Shen et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were reported in the literature for soy protein networks with lower concentrations. Shen et al reported for a soy yoghurt that the hardness of the yoghurt increases with the decrease in pH [ 35 ]. For heat-induced SPI gels, Renkema found that stronger networks were formed closer to the IEP due to the increased attractive interaction energy [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pH values of soy yogurt were determined by a pH meter (ST3100-F; OHAUS). The TA was determined by a titration method using 0.1 mol/L sodium hydroxide according to the method of Shen et al (2021). Before the analysis, 10 g of the sample was accurately weighed and mixed with 20 mL of deionized water, and the titration was performed using phenolphthalein as an indicator.…”
Section: Ph and Ta Measurementmentioning
confidence: 99%